2019
DOI: 10.1016/j.physio.2018.11.305
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of an innovative day surgery pathway for unicompartmental knee replacement: no need for early knee flexion

Abstract: Objectives To evaluate the introduction of an innovative rehabilitation protocol, delaying knee flexion, for patients receiving unicompartmental knee replacement. Design Longitudinal cohort. Setting Specialist Orthopaedic Unit within an NHS Foundation Trust. Participants 669 consecutive patients undergoing unicompartmental knee replacement. Intervention An innovative rehabilitation protocol, delaying knee flexion. Main Outcome Measures Length of stay, range of movement, Surgical Satisfaction Questionnaire. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…This resulted in a higher mean ASA score in patients compared with the above-mentioned studies, and a very large range in both patient age and BMI. This large range in patient demographics in an unselected cohort was also reported by Jenkins et al (2019). Furthermore, all patients in our study were discharged to their own homes with no additional care.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…This resulted in a higher mean ASA score in patients compared with the above-mentioned studies, and a very large range in both patient age and BMI. This large range in patient demographics in an unselected cohort was also reported by Jenkins et al (2019). Furthermore, all patients in our study were discharged to their own homes with no additional care.…”
Section: Discussionsupporting
confidence: 73%
“…We found that 22% of unselected patients were discharged on DOS. A study by Jenkins et al (2019) reported 39% (n = 669) of consecutive unselected unilateral UKA patients to be discharged on DOS. The aim of that study was to investigate the effect of delaying knee flexion on different outcome measures such as LOS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations